Implementasi Platform Edukasi Pada Klinik Medikasih Pondok Kelapa Jakarta Timur - Akbar, Yuma; Maulana, Rizki; Ramadhan, Muhammad Arya; Sibarani, Julvan Marzuki Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Medikasih Clinic, which is located in Pondok Kelapa Village, Duren Sawit District, East Jakarta City, Special Capital Region of Jakarta, currently relies on a paid platform to manage clinic operations. However, there is no specific health education platform available for patients/customers, and the importance of improving the quality of health services at this clinic is highly recognized. To overcome these challenges, the service team plans to launch a web-based health education platform. This platform aims to support increased patient participation and health literacy by presenting health information from various medical sources. Based on the analysis of popular medical record diagnoses at Medikasih Clinic, we are determined to provide users with easy and reliable access to understanding health conditions, preventive measures, and healthy lifestyle practices. In conclusion, the development of this platform is a progressive step to create a positive impact. A focus on increasing health literacy and patient participation will create a society that is more informed and involved in personal health management. Our recommendation is to engage health experts and specialists to contribute educational content, ensuring the accuracy and reliability of the information presented